PROTOCOOPERATIVE SOCIAL NETWORKS - Tatiana de Carvalho DUARTE (Fonseca, Journal of Communication, 2023)
This work makes use of interdisciplinarity with biology, to build a concept that explains the current configuration of Web 2.0, its expansion and growth. To illustrate the process, I used the analogy with the ecological relationships that can be established based on interactions between neutral, positive or negative species.